Metabolism of 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine by Mitochondrion-targeted Cytochrome P450 2D6: IMPLICATIONS IN PARKINSON DISEASE - Bajpai, Prachi (American Society for Biochemistry and Molecular Biology, 2013)
1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) is a neurotoxic side product formed in the chemical synthesis of desmethylprodine opioid analgesic, which induces Parkinson disease. Monoamine oxidase B, present in the mitochondrial outer membrane of glial cells, catalyzes the oxidation of MPTP to the toxic 1-methyl-4-phenylpyridinium ion (MPP(+)), which then targets the dopaminergic neurons causing neuronal death. Here, we demonstrate that mitochondrion-targeted human cytochrome P450 2D6 (CYP2D6), supported by mitochondrial adrenodoxin and adrenodoxin reductase, can efficiently catalyze the metabolism of MPTP to MPP(+), as shown with purified enzymes and also in cells expressing mitochondrial CYP2D6. Neuro-2A cells stably expressing predominantly mitochondrion-targeted CYP2D6 were more sensitive to MPTP-mediated mitochondrial respiratory dysfunction and complex I inhibition than cells expressing predominantly endoplasmic reticulum-targeted CYP2D6. Mitochondrial CYP2D6 expressing Neuro-2A cells produced higher levels of reactive oxygen species and showed abnormal mitochondrial structures. MPTP treatment also induced mitochondrial translocation of an autophagic marker, Parkin, and a mitochondrial fission marker, Drp1, in differentiated neurons expressing mitochondrial CYP2D6. MPTP-mediated toxicity in primary dopaminergic neurons was attenuated by CYP2D6 inhibitor, quinidine, and also partly by monoamine oxidase B inhibitors deprenyl and pargyline. These studies show for the first time that dopaminergic neurons expressing mitochondrial CYP2D6 are fully capable of activating the pro-neurotoxin MPTP and inducing neuronal damage, which is effectively prevented by the CYP2D6 inhibitor quinidine.